Review of The Wiley Blackwell Companion to Contemporary British and Irish Literature, by Richard Bradford et al., eds. - Lianghui Li (Review of Irish Studies in Europe)
Review of The Wiley Blackwell Companion to Contemporary British and Irish Literature, by Richard Bradford et al., eds. (Hoboken, NJ: Wiley-Blackwell, 2020). 912pp., ISBN 9781118902301 (hardback)